Preparation of g-C3N4/AgIn(MoO4)2 and its photocatalytic degradation of tetracycline hydrochloride - Jia Lijun; Zhang Qianqian; Yan Xu; Zeng Ke (E3S Web of Conferences, 2021)
Graphite phased carbon nitride and indium silver molybdate [g-C3N4 / AgIn(MoO4)2]photocatalytic materials were prepared by hydrothermal method. X-ray diffraction, transmission electron microscope, scanning electron microscope, X-ray photoelectric spectrum, UV-vis diffuse reflection spectrum and solid fluorescence were used to analyze its structure and morphology. The results showed that the catalytic activity of g-C3N4 / AgIn(MoO4)2 was significantly higher than that of pure g-C3N4 and AgIn(MoO4)2 under visible light irradiation. Under the conditions of g-C3N4 and AgIn(MoO4)2 with a compound ratio of 2:1 and hydrothermal reaction at 120℃ for 6 hours, the degradation efficiency of tetracycline hydrochloride was the best. After 1 hour of light reaction, the degradation rate of tetracycline hydrochloride could reach 75.3%. g-C3N4/AgIn(MoO4)2 is expected to be a promising photocatalyst for wastewater treatment.